2012
DOI: 10.11005/kjbm.2012.19.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Routine Application of the Korean FRAX Model in Women: a Single-center Study

Abstract: = Abstract =Objectives: The objective of this study was to assess the efficacy of the Korean fracture-risk assessment tool (FRAX) model for routine application in women who had a general check-up for bone mineral density (BMD). Methods: This retrospective study was conducted at a university hospital and comprised 343 patients, whose BMD and clinical risk factors were assessed for FRAX calculation. The 10-year probabilities of hip and major osteoporotic fractures were compared with the result of the FRAX ® tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[1] Recently, the fracture-risk assessment tool (FRAX) using clinical risk factors and measures of femoral neck bone mineral density (BMD) is used to predict the fracture probability. [2] The exact diagnosis and prediction of osteoporosis and identification of osteoporosis risk factors are important; however, prevention is also important. Prevention of osteoporosis should be addressed from a young age.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Recently, the fracture-risk assessment tool (FRAX) using clinical risk factors and measures of femoral neck bone mineral density (BMD) is used to predict the fracture probability. [2] The exact diagnosis and prediction of osteoporosis and identification of osteoporosis risk factors are important; however, prevention is also important. Prevention of osteoporosis should be addressed from a young age.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reviewed the Korean FRAX model with the general population and recommended that physicians use the Korean FRAX model in the general female population to predict fracture risk. [ 3 ] We already found that serum (25-[OH]D 3 ) concentrations were significantly correlated with age ( P =0.001), duration of menopause ( P =0.005), and osteoporosis ( P =0.044). [ 4 ]…”
Section: Discussionmentioning
confidence: 97%